PELATIHAN ARTIFICIAL INTELLIGENCE UNTUK PENINGKATAN LITERASI DIGITAL REMAJA PEDESAAN: STUDI PENGABDIAN BERBASIS INTERVENSI - Erlan Darmawan; Nani Ronsani Thamrin; Dewi Sukma Nurhana; Tiara Astuti; Rohmalia; Aditiya; Muhammad Pakhriz Alif (Jurnal Abdi Inovatif : Pengabdian kepada Masyarakat, 2026)
This community service program was implemented to address low digital literacy among rural youth and to provide limited access to Artificial Intelligence (AI) training. Although smartphone usage among teenagers is quite high, it remains largely focused on entertainment and social media, so the productive use of digital technology has not developed to its full potential. To address this, the activity was carried out with youth from Pajawan Kidul Village, Lebakwangi District, Kuningan Regency, aiming to improve their basic understanding of AI and digital literacy skills in rural areas. The implementation method used a participatory approach through socialization, AI practice, mentoring, project-based learning, and evaluation using pre- and posttests. During this process, participants received training on using various AI-based applications, including ChatGPT, QuillBot, Canva AI, and Tome AI. In total, 30 village youth were involved in all program activities. As a result, the activity showed an increase in participants' understanding of AI concepts and their application in daily activities. The average score of participants increased from 57.44 before the training to 82.66 after the activity ended, an increase of approximately 43.9%. Notably, there was significant growth in participants' understanding of how AI can support more productive activities. Beyond improving participants' skills, this activity led to five AI-based mini-projects and the formation of the "Youth Tech Club Pajawan Kidul" learning community to sustain digital learning in the village. In summary, AI training that emphasizes hands-on practice and a contextual approach can be an effective way to strengthen digital literacy while reducing the technology gap among rural youth.